Cross-Sectional and Longitudinal Associations Between Plasma Neurodegenerative Biomarkers and Physical Performance Among Community-Dwelling Older Adults. (13th November 2020) - He, Lingxiao; de Souto Barreto, Philipe; Giudici, Kelly V; Aggarwal, Geetika; Nguyen, Andrew D; Morley, John E; Li, Yan; Bateman, Randall J; Vellas, Bruno; ,
Abstract: Background: Plasma amyloid-beta (Aβ), neurofilament light chain (NfL), and progranulin (PGRN) have been related to multiple neurodegenerative conditions that might affect physical performance. The aim of this study was to explore the relationship between these plasma neurodegenerative markers and physical performance among community-dwelling older adults. Methods: Five hundred and seven older adults (aged 76 ± 5 years) previously recruited in the Multidomain Alzheimer's Preventive Trial, and had received blood and physical performance tests, were included in this study. Plasma Aβ (Aβ 42 /Aβ 40 ratio), NfL, and PGRN levels were measured. Physical performance was assessed by handgrip strength and the Short Physical Performance Battery (combining gait speed, chair stands, and balance tests). Physical performance measured at the same time point and after the blood tests were used. Mixed-effect linear models were performed with age, sex, allocation to Multidomain Alzheimer's Preventive Trial group, body mass index, and Mini-Mental State Examination score as covariates. Results: The mean values of Aβ 42 /Aβ 40 ratio, NfL, and PGRN were 0.11, 84.06 pg/mL, and 45.43 ng/mL, respectively. At the cross-sectional level, higher plasma NfL was associated with a lower Short Physical Performance Battery score (β = −0.004, 95% CI [−0.007, −0.001]). At the longitudinal level, higher PGRN levels were associated with decreasing handgrip strength over time (β = −0.02, 95% CI [−0.04, −0.007]). All the other associations were statistically nonsignificant. Conclusion: Our findings suggest the possibility of using plasma NfL and PGRN as markers of physical performance in older adults.